Investigating Pharmacists Perceptions and Engagement with Generative AI in Everyday Contexts and Decision-Making - Bachina, Lakshmipriya; Anusha, Kanagala; Pallerla, Niveditha (International Journal of Pharmaceutical Investigation, 2026)
Aim/Background Generative Artificial Intelligence (Generative AI or Gen AI) is a subset of Artificial Intelligence that produces multimedia content, including text, images, stories, videos, music, and other digital artifacts. Gen AI leverages the deep learning techniques and large language models is to generate human-like text and advanced innovative outputs. The study investigates the public perception, engagement, trust and decision-making related information by using Generative AI tools in individuals’ daily life. Materials and Methods Data was collected from 180 individuals who are using current Generative AI applications regularly to support their work. By using Jamovi software Reliability analysis conducted and Cronbach’s alpha showed in 0.815, it indicates strong internal consistency. Exploratory Factor Analysis (EFA) was conducted to validate the measurement model and followed by multiple regression analysis is to examine the relationship between public perception, engagement, trust, and decision-making. Results Results revealed that trust and decision-making were not statistically significant (p=0.630) in most cases, suggesting that the Pharmacists perceptions of Generative AI as innovative, they do not fully embrace it, and trust remains limited. Conclusion The study concluded that the Pharmacists perception of Generative AI as innovative, limited trust and remains a barrier to a full adoption and highlighting the need for strategies that enhance the transparency, reliability and ethical safeguards to support its use in everyday decision-making.
Keywords: Generative AI; Pharmacist Perception; Engagement; Decision Making; Trust.